In situ evaluation of orthodontic elastomeric chains - Baratieri,Carolina (2012)
The hypothesis tested in this study was that intraoral exposure of elastomeric chains alters their tensile strength. For such purpose, it was evaluated the in situ behavior of different elastomeric chains stretched for 3 weeks. Three kinds of elastomeric chains, Plastic chain (PC), Memory chain (MC) and Super slick chain (SSC), were randomly placed in 3 quadrants of 13 patient in a fixed distance of 16 mm and mean initial force of 180 g. Tensile testing was performed in an universal testing machine at different intervals: initial, 1 h, 24 h, 1 week, 2 weeks and 3 weeks. A two-way ANOVA test was performed to identify the influence of both material and time on the force decrease. A subsequent one-way ANOVAtest with the Tukey's post hoc test was used to identify statistically significant intragroup and intergroup remaining force (g and %) differences at 5% significance level. The effect of both the material and the time factors were significant. All groups showed significant force decrease after the 1-h period (23% for PC and 14% for MC and SSC). At the end of the 3-week period, the remaining force was 57% (96 g), 67% (129 g) and 71% (125 g) for PC, MC and SSC, respectively. In conclusion, intraoral exposure of elastomeric chains altered their tensile strength. In general, the greater force decrease occurred within the first hour. The remaining force of the enhanced chains measured at each time interval was greater than the conventional one (PC). After 3 weeks, only the enhanced chains maintained the force applied over 100 g.